Non-contentious procedure before a notary - Tarazona Alvarado, Fernando (2021)
This year marks 25 years since the enactment of Law No. 26662, a rule by which notaries were granted powers so that they can hear, alternatively, the Judiciary, certain non-contentious matters, this being a longstanding request for both the doctrine as of the International Union of Latin Notaries, due to the fact that these are procedures where there is no litigation, and therefore, perfectly acceptable by notaries due to their notarial function, thereby contributing to the decongestion of the judiciary. Various countries in Europe, America and Asia, with the presence of Latin notaries, have been granting notaries powers to process non-contentious matters, Peru being the exception. Although law No. 26662 initially collected only six non-contentious cases, later others were added, due to the reception it had among the population, given the speed with which they are processed. However, it should be noted that all non-contentious matters where evidence is not necessary have not yet passed to the notarial jurisdiction, and this must occur given the advantages it represents for society.